2007
DOI: 10.1007/s00221-007-1186-7
|View full text |Cite
|
Sign up to set email alerts
|

Acute perinatal asphyxia impairs non-spatial memory and alters motor coordination in adult male rats

Abstract: A large body of clinical evidence suggests a possible association between perinatal asphyxia and the onset of early, as well as long-term, neurological and psychiatric disorders including cognitive deficits. The present study investigated cognitive and motor function modifications in a well characterized and clinically relevant experimental rat model of human perinatal asphyxia. The results reported here show that adult rats exposed to a single (20 min) asphyctic episode at delivery displayed: (a) a deficit in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 54 publications
3
39
0
3
Order By: Relevance
“…A reduction in the desire to explore is unlikely to contribute to the deficit, as there was no difference between C-section-delivered and asphyxiated offspring in the time spent exploring objects overall (novel plus familiar). Previous studies have demonstrated impaired spatial memory as a result of birth asphyxia [22] , but our study suggests that birth asphyxia impaired both the ability to remember task-associated information (i.e., the rotarod), and non-spatial memory (the NORT). Our findings are consistent with a recent study of birth asphyxia in the term fetal rat (though, using 20 min of asphyxia), which showed impaired non-spatial memory using NORT, although the survival rate of the asphyxiated offspring was not reported and only data for male offspring were presented [22] .…”
Section: Discussionmentioning
confidence: 40%
“…A reduction in the desire to explore is unlikely to contribute to the deficit, as there was no difference between C-section-delivered and asphyxiated offspring in the time spent exploring objects overall (novel plus familiar). Previous studies have demonstrated impaired spatial memory as a result of birth asphyxia [22] , but our study suggests that birth asphyxia impaired both the ability to remember task-associated information (i.e., the rotarod), and non-spatial memory (the NORT). Our findings are consistent with a recent study of birth asphyxia in the term fetal rat (though, using 20 min of asphyxia), which showed impaired non-spatial memory using NORT, although the survival rate of the asphyxiated offspring was not reported and only data for male offspring were presented [22] .…”
Section: Discussionmentioning
confidence: 40%
“…In rodents, both perinatal asphyxia and postnatal hypoxia impaired SOR. Asphyxia on the last day of gestation led to impaired SOR with a 1-h delay when the animals were tested as adults (Simola et al 2008;Morales et al 2010). Performance was intact with a 15-min delay, arguing against a non-mnemonic explanation for the deficit (Simola et al 2008).…”
Section: Neurodevelopmental Modelsmentioning
confidence: 95%
“…Asphyxia on the last day of gestation led to impaired SOR with a 1-h delay when the animals were tested as adults (Simola et al 2008;Morales et al 2010). Performance was intact with a 15-min delay, arguing against a non-mnemonic explanation for the deficit (Simola et al 2008). Conversely, a single episode of hypoxia-ischaemia (HI) on P7 led to impaired SOR in adolescent rats, using a delay of only 5 min (Pereira et al 2008).…”
Section: Neurodevelopmental Modelsmentioning
confidence: 95%
“…No gross morphology indicating necrotic cell death has been found in rat pups surviving short- or long-periods of perinatal asphyxia, when the main experimental parameter is anoxia (Dell’Anna et al 1997). Nevertheless, several neurochemical and immunocytochemical studies have shown specific neuronal changes at short (Dell’Anna et al 1995; Chen et al 1997a), and extended time intervals after the insult (Andersson et al 1995; Dell’Anna et al 1997, Chen et al 1997a, b, c), which may explain behavioural and cognitive deficits occurring with a delayed onset (Chen et al 1995; Simola et al 2008; Morales et al 2010). …”
Section: Early and Delayed Cell Deathmentioning
confidence: 99%
“…In the rat, several studies have investigated the behavioural effects associated with perinatal asphyxia, addressing motor function (Bjelke et al 1991; Chen et al 1995), emotional behaviour (Dell’Anna et al 1991, Hoeger et al 2000; Venerosi et al 2004, 2006, Simola et al 2008; Morales et al 2010), and spatial memory (Boksa et al 1995; Iuvone et al 1996; Hoeger et al 2000, 2006; Loidl et al 2000; Van de Berg et al 2003; Venerosi et al 2004). …”
Section: Behavioural and Cognitive Deficitsmentioning
confidence: 99%